Redox Profiling of Selected Apulian Red Wines in a Single Minute - Douglas Vieira Thomaz; Renê Oliveira do Couto; Riccardo Goldoni; Cosimino Malitesta; Elisabetta Mazzotta; Gianluca Martino Tartaglia (MDPI AG, 2022)
Wine is a complex bioproduct whose chemical composition is highly variable across production regions. In order to shed light on affordable ways to promote the characterization of wines and explore the physicochemical basis of their antioxidant capacity, this work reported on the quick and easy redox profiling of selected red wines from Apulia, Italy. Therefore, an affordable and quickly performed semiempirical quantum chemistry approach, i.e., the extended Hückel method, was used to compute the bandgaps of the main phytochemical markers attributed to red wines. The findings of these calculations were then compared to an electroanalytical investigation in the form of cyclic and square-wave voltammetry, and the electric current of the redox profiles was used as the input dataset for principal component analysis. Results showcased that the semiempirical quantum chemistry calculations allowed the correlation of the bandgaps to the observed faradaic signals upon voltammetry; thereby, also providing insights on their antioxidant appeal by highlighting the feasibility of charge-transfer processes at low electric potentials. Furthermore, the principal component analysis showed that the electric current dataset gathered in a time span of 55 s allowed the appropriate separation of the samples, which hints at the possible use of quick voltammetric assays as fingerprinting tools.